A novel approach for rapid screening of mitochondrial D310 polymorphism - GÜLLÜOĞLU, MAHMUT BAHADIR; AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (BMC, 2006)
Background: Mutations in the mitochondrial DNA ( mtDNA) have been reported in a wide variety of human neoplasms. A polynucleotide tract extending from 303 to 315 nucleotide positions (D310) within the non-coding region of mtDNA has been identified as a mutational hotspot of primary tumors. This region consists of two polycytosine stretches interrupted by a thymidine nucleotide. The number of cytosines at the first and second stretches are 7 and 5 respectively, according to the GeneBank sequence. The first stretch exhibits a polymorphic length variation (6-C to 9-C) among individuals and has been investigated in many cancer types. Large-scale studies are needed to clarify the relationship between cytosine number and cancer development/progression. However, time and money consuming methods such as radioactivity-based gel electrophoresis and sequencing, are not appropriate for the determination of this polymorphism for large case-control studies. In this study, we conducted a rapid RFLP analysis using a restriction enzyme, BsaXI, for the single step simple determination of 7-C carriers at the first stretch in D310 region. Methods: 25 colorectal cancer patients, 25 breast cancer patients and 41 healthy individuals were enrolled into the study. PCR amplification followed by restriction enzyme digestion of D310 region was performed for RFLP analysis. Digestion products were analysed by agarose gel electrophoresis. Sequencing was also applied to samples in order to confirm the RFLP data. Results: Samples containing 7-C at first stretch of D310 region were successfully determined by the BsaXI RFLP method. Heteroplasmy and homoplasmy for 7-C content was also determined as evidenced by direct sequencing. Forty-one percent of the studied samples were found to be BsaXI positive. Furthermore, BsaXI status of colorectal cancer samples were significantly different from that of healthy individuals. Conclusion: In conclusion, BsaXI RFLP analysis is a simple and rapid approach for the single step determination of D310 polymorphism of mitochondrial DNA. This method allows the evaluation of a significant proportion of samples without the need for sequencing- and/or radioactivity-based techniques.
Keywords: DNA MUTATIONS; MONONUCLEOTIDE REPEAT; BREAST-CANCER; TUMORS; GENOME